Equatorial secondary cosmic ray observatory to study space weather and terrestrial events. Issue 10 (15th May 2018) - Vichare, Geeta; Bhaskar, Ankush; Datar, Gauri; Raghav, Anil; Nair, K.U.; Selvaraj, C.; Ananthi, M.; Sinha, A.K.; Paranjape, M.; Gawade, T.; Anil Kumar, C.P.; Panneerselvam, C.; et al.
Highlights: Recent installation of equatorial secondary cosmic ray observatory (ESCRO) at Tirunelveli, India. Details of experimental set up, Performance and calibration of NaI(Tl) scintillation detectors. Hysteresis effect observed in gain drift (shift in channel numbers) due to temperature variations. Abstract: Recently, equatorial secondary cosmic ray observatory has been established at Equatorial Geophysical Research Laboratory (EGRL), Tirunelveli, (Geographic Coordinates: 8.71°N, 77.76°E), to study secondary cosmic rays (SCR) produced due to the interaction of primary cosmic rays with the Earth's atmosphere. EGRL is a regional center of Indian Institute of Geomagnetism (IIG), located near the equator in the Southern part of India. Two NaI(Tl) scintillation detectors are installed inside the temperature controlled environment. One detector is cylindrical in shape of size 7.62 cm × 7.62 cm and another one is rectangular cuboid of 10.16 cm × 10.16 cm × 40.64 cm size. Besides NaI(Tl) detectors, various other research facilities such as the Geomagnetic observatory, Medium Frequency Radar System, Digital Ionosonde, All-sky airglow imager, Atmospheric electricity laboratory to measure the near-Earth atmospheric electric fields are also available at EGRL. With the accessibility of multi- instrument facilities, the objective is set to understand the relationship between SCR and various atmospheric and ionospheric processes, during space weather and terrestrial events. For gamma-ray spectroscopy, it is important to test the performance of the NaI(Tl) scintillation detectors and to calibrate the gamma-ray spectrum in terms of energy. The present article describes the details of the experimental setup installed near the equator to study cosmic rays, along with the performance testing and calibration of the detectors under various conditions. A systematic shift in the gain is observed with varying temperature of the detector system. It is found that the detector's response to the variations in the temperature is not just linear or non-linear type, but it depends on the history of the variation, indicating temperature hysteresis effects on NaI detector and PMT system. This signifies the importance of isothermal environment while studying SCR flux using NaI(Tl) detectors, especially for the experiments conducted during daytime such as solar eclipses etc.